2023
DOI: 10.3389/fped.2022.1072851
|View full text |Cite
|
Sign up to set email alerts
|

Experience with clinical cerebral autoregulation testing in children hospitalized with traumatic brain injury: Translating research to bedside

Abstract: ObjectiveTo report our institutional experience with implementing a clinical cerebral autoregulation testing order set with protocol in children hospitalized with traumatic brain injury (TBI).MethodsAfter IRB approval, we examined clinical use, patient characteristics, feasibility, and safety of cerebral autoregulation testing in children aged <18 years between 2014 and 2021. A clinical order set with a protocol for cerebral autoregulation testing was introduced in 2018.Results25 (24 severe TBI and 1 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
3
1
Order By: Relevance
“…Our study shows that some patients may benefit from MAP augmentation but the observed heterogeneity in PbtO 2 patterns with MAP augmentation suggests that other factors that affect PbtO 2 must be considered, to identify which patients with severe TBI will be PbtO 2 responders to MAP augmentation (15). For example, cerebral autoregulation is often impaired in patients with severe TBI and can result in cerebral hypoperfusion, cerebral hypoxia, and cerebral ischemia and while we did not detect a relationship between impaired cerebral autoregulation status and PbtO 2 pattern, cerebrovascular pressure reactivity methods are reported to correlate CPP changes with changes in PbtO 2 (16)(17)(18)(19). An observational study of 38 patients with severe TBI showed that PbtO 2 was pressure-dependent when cerebral autoregulation was impaired and stable if cerebral autoregulation was intact (20) and data from another observational study of 77 patients found a shorter plateau in a triphasic response between PbtO 2 and CPP, with cerebrovascular pressure reactivity impaired compared to when it was intact (11).…”
Section: Resultscontrasting
confidence: 71%
“…Our study shows that some patients may benefit from MAP augmentation but the observed heterogeneity in PbtO 2 patterns with MAP augmentation suggests that other factors that affect PbtO 2 must be considered, to identify which patients with severe TBI will be PbtO 2 responders to MAP augmentation (15). For example, cerebral autoregulation is often impaired in patients with severe TBI and can result in cerebral hypoperfusion, cerebral hypoxia, and cerebral ischemia and while we did not detect a relationship between impaired cerebral autoregulation status and PbtO 2 pattern, cerebrovascular pressure reactivity methods are reported to correlate CPP changes with changes in PbtO 2 (16)(17)(18)(19). An observational study of 38 patients with severe TBI showed that PbtO 2 was pressure-dependent when cerebral autoregulation was impaired and stable if cerebral autoregulation was intact (20) and data from another observational study of 77 patients found a shorter plateau in a triphasic response between PbtO 2 and CPP, with cerebrovascular pressure reactivity impaired compared to when it was intact (11).…”
Section: Resultscontrasting
confidence: 71%
“…Patient factors, such as systemic hypertension, bradycardia, and high ICP, were transient and required no medical intervention. However, we think that testing environments should include plans for treating sustained or severe hypertension, high ICP, and bradycardia and that rates of adverse events are consistent with our prior experience [ 12 ]. Static cerebral autoregulation testing is a provocative challenge test that appears to add additional value to multimodal neuromonitoring, and this deserves further study.…”
Section: Discussionsupporting
confidence: 68%
“…Cerebral autoregulation studies are performed by one certified cerebrovascular laboratory technologist. An electronic order set [ 12 ] details the desired type of cerebral autoregulation testing (static or dynamic), as well as baseline and testing boundaries and conditions. Given the large number of patients with TBI who have polytrauma, static cerebral autoregulation testing is preferred to thigh cuff methods [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Since TCDbased techniques rely on provocative testing during which MAP is augmented, some patients may experience excessive systemic hypertension, bradycardia, or intracranial hypertension during testing. 8 Hence, careful patient selection, including the consideration of baseline intracranial pressure (ICP), vasopressor requirement and PaCO 2 levels during the pre-testing review, is essential to avoid incomplete testing due to patients' exposure to undesirable cerebrovascular targets. In contrast, continuous dynamic CA testing relies on the presence of an ICP monitoring device and thus restricts its use to patients with this monitoring in place.…”
Section: Introductionmentioning
confidence: 99%